The Advances and Biomedical Applications of Imageable Nanomaterials - Xiang, Xiaohong; Shi, Doudou; Gao, Jianbo (Frontiers in Bioengineering and Biotechnology, 2022)
Imaging technology plays an important role in screening, diagnosing and treating diseases. However, given the limitations of current imaging technology, the efficacy of some smaller lesions and dynamic monitoring drugs still cannot be traced in vitro and in real-time. In addition, nanomaterials have been proven to contribute to the diagnosis and treatment of human diseases due to their small molecular weight, low immunogenicity, special modifications and properties such as acoustics and optics. With the advancement of nanotechnology, researchers have produced various nanomaterials with imaging capabilities which have shown great potential in biomedical research. Here, we summarized the research based on the characteristics of imageable nanomaterials, highlighted the advantages and biomedical applications of imageable nanomaterials in the diagnosis and treatment of diseases, and discussed current challenges and prospects.